2014
DOI: 10.1515/rnam-2014-0015
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a kink movement in homogeneous and heterogeneous DNA sequences taking into account the dissipation

Abstract: The problem of modelling the movement of a nonlinear conformational perturbation (i.e., kink) along a DNA molecule is considered taking into account the dissipation. The study of movement peculiarities is performed using a homogeneous sequence of nucleotides and a heterogeneous one consisting of two homogeneous parts separated by a boundary. Using analytic and numerical methods, it is shown that the effect of dissipation leads to a decrease of the energy of kink E, its velocity v, and the mass M. It is also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This potential does not contribute to the total energy of the system (vanishes) only when the base pairs form a spiral. Substituting (2), (3), (4) and (5) (6) where m is the nucleotide mass, F n (t) is an external stochastic force. For the convenience of studying the model, the dimensionless Hamilton function is obtained.…”
Section: Equations Of Motion Of the Dna Nucleotides And Their Approximentioning
confidence: 99%
See 1 more Smart Citation
“…This potential does not contribute to the total energy of the system (vanishes) only when the base pairs form a spiral. Substituting (2), (3), (4) and (5) (6) where m is the nucleotide mass, F n (t) is an external stochastic force. For the convenience of studying the model, the dimensionless Hamilton function is obtained.…”
Section: Equations Of Motion Of the Dna Nucleotides And Their Approximentioning
confidence: 99%
“…It is a complex dynamic system consisting of many atoms and has a quasi-one-dimensional structure with specific symmetry, multiple degrees of freedom, and many types of movements and a special distribution of internal interactions [1]. These functions of DNA are discussed in some DNA models to investigate the relationship of structural-dynamic and functional properties of the molecule [2][3][4][5][6][7][8][9][10][11][12][13]. A comprehensive review on the DNA properties can be found in the work [14].…”
Section: Introductionmentioning
confidence: 99%